Image generation from freehand sketches using Diffusion Models - Tanvir, Farhan; Haque, Md. Fahim; Islam, Kazi Rifatul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.